1996
DOI: 10.1111/j.1365-2605.1996.tb00448.x
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical detection of immature Sertoli cell markers in testicular tissue of infertile adult men: a preliminary study

Abstract: Testicular biopsy specimens from oligozoospermic infertile patients are characterized by different types of spermatogenic impairment in adjacent seminiferous tubules, a phenomenon called mixed atrophy. In order to evaluate possible involvement of the state of Sertoli cell differentiation, the distribution pattern of anti-Müllerian hormone (AMH), vimentin and cytokeratin intermediate filament proteins was investigated by means of immunohistochemistry. AMH immunoactivity occurs in Sertoli cells of the normal pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
61
0
4

Year Published

2001
2001
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 114 publications
(69 citation statements)
references
References 24 publications
4
61
0
4
Order By: Relevance
“…This interpretation is reinforced by studies in patients with complete AIS, in whom the Sertoli cells retain immature morphological and functional features such as expression of AMH (Rajpert-de Meyts et al, Regadera et al, 1999;Rey et al, 1999). Moreover, in some men with impaired spermatogenesis, especially those who exhibit focal SCO with morphologically immature Sertoli cells, focal expression of AMH and cytokeratin 18 (Steger et al, 1996;Rajpert-de Meyts et al, 1999;Maymon et al, 2000Maymon et al, , 2002 and absence of AR expression (Regadera et al, 2001) are evident, consistent with failure of maturation of Sertoli cells in these regions. A similar association is frequently seen in men with testicular germ-cell cancer, in particular the association of Sertoli cells with an immature phenotype and the presence of pre-cancerous CIS cells ( Fig.…”
Section: Immunohistochemical Evidence For Immaturity Of Sertoli Cellsmentioning
confidence: 85%
See 1 more Smart Citation
“…This interpretation is reinforced by studies in patients with complete AIS, in whom the Sertoli cells retain immature morphological and functional features such as expression of AMH (Rajpert-de Meyts et al, Regadera et al, 1999;Rey et al, 1999). Moreover, in some men with impaired spermatogenesis, especially those who exhibit focal SCO with morphologically immature Sertoli cells, focal expression of AMH and cytokeratin 18 (Steger et al, 1996;Rajpert-de Meyts et al, 1999;Maymon et al, 2000Maymon et al, , 2002 and absence of AR expression (Regadera et al, 2001) are evident, consistent with failure of maturation of Sertoli cells in these regions. A similar association is frequently seen in men with testicular germ-cell cancer, in particular the association of Sertoli cells with an immature phenotype and the presence of pre-cancerous CIS cells ( Fig.…”
Section: Immunohistochemical Evidence For Immaturity Of Sertoli Cellsmentioning
confidence: 85%
“…In humans, cytokeratin 18 is a robust marker of immature Sertoli cells and in adult testes it has been used to identify seminiferous tubules in which the Sertoli cells have not matured (Stosiek et al, 1990;Steger et al, 1996Steger et al, , 1999Maymon et al, 2000), though this has also been indicated as reflecting de-differentiation of mature Sertoli cells (Kliesch et al, 1998;Steger et al, 1999).…”
Section: Cytokeratin 18mentioning
confidence: 99%
“…According to Matsumoto et al [29], we should have quantitatively a normal spermatogenesis in these patients; nevertheless, the number of Sertoli cells is important to consider and a good correlation between the sperm production and that parameter has been reported [23]. Besides the immunological FSH value, the biopotency of FSH should be also taken into account as well as the presence of IgG antibodies [16,22,46,48]. In idiopathic infertile men, there are no IgG antibodies against FSH and frequently the bioactive FSH level is not altered [4].…”
Section: Discussionmentioning
confidence: 99%
“…Besides the special architecture of the Sertoli cells [10,43], the presence of integrins and cadherins, which are involved in the cell-cell adhesion, has been reported [31]. With the availability of specific primers, reverse transcription-polymerase chain reaction studies have been developed and microdeletions of the Y chromosome have been discovered in infertile men [39,48]. In spite of the high potency of these tools we still do not have any specific treatment to propose in case of idiopathic infertility in men with normal FSH levels.…”
mentioning
confidence: 99%
“…One of these proteins is cytokeratin 18, an intermediate filament protein, which is consistently expressed in immature Sertoli cells of (normal) prepubertal seminiferous tubules, but is completely absent in normal, mature seminiferous tubules [1]. Cytokeratin 18 immunoactivity was found in Sertoli cells of tubules showing spermatogenic arrest at the level of spermatogonia and in some Sertoli cell only tubules with immature Sertoli cells which are frequently observed within so-called mixed atrophy biopsies [1][2][3][4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%